Building Social Construction and Tolerance In Customary Communication Law Communities (Study of Local Wisdom of Malay Tribes) - Marwan, Marwan; Alamsyah, Alamsyah (Dinasti Research, 2024)
The purpose of this study is to find the meaning and positive role of the culture of